1986
DOI: 10.1073/pnas.83.19.7443
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of type II collagen-induced arthritis by intragastric administration of soluble type II collagen.

Abstract: Although oral administration of protein antigens may lead to specific immunologic unresponsiveness, this method of immunoregulation has not been applied to models of autoimmune disease. Type II collagen-induced arthritis is an animal model of polyarthritis induced in susceptible mice and rats by immunization with type II collagen, a major component of cartilage. Intragastric administration of soluble type II collagen, prior to immunization with type II collagen in adjuvant, suppresses the incidence of collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
156
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(164 citation statements)
references
References 33 publications
6
156
0
2
Order By: Relevance
“…The oral tolerogenicity of heated proteins was demonstrated after prolonged feeding of whey proteins prepared at 90ЊC for 1 h [13], but was questioned by two other reports [14,15]. One reported that collagen-induced arthritis could be suppressed by feeding soluble type II collagen, but not type II collagen heated at 56ЊC for 45 min [14]. The other reported that deaggregated human r-globulin was better than human r-globulin heat aggregated at 63ЊC for 25 min in the induction of oral tolerance [15].…”
Section: Introductionmentioning
confidence: 99%
“…The oral tolerogenicity of heated proteins was demonstrated after prolonged feeding of whey proteins prepared at 90ЊC for 1 h [13], but was questioned by two other reports [14,15]. One reported that collagen-induced arthritis could be suppressed by feeding soluble type II collagen, but not type II collagen heated at 56ЊC for 45 min [14]. The other reported that deaggregated human r-globulin was better than human r-globulin heat aggregated at 63ЊC for 25 min in the induction of oral tolerance [15].…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of antigens is a long-recognized method for inducing systemic immunological tolerance (1,2), and has been proposed as an approach for the treatment or prevention of allergic (3)(4)(5) and autoimmune diseases (6)(7)(8)(9)(10)(11)(12)(13). This approach, however, requires administration of massive amounts of antigens or prolonged feeding of small amounts of antigens, which are then only effective in rather narrow dose ranges.…”
mentioning
confidence: 99%
“…Because of an apparently low risk of adverse effects, a promising approach of Th1/Th2 immune deviation is the mucosal administration of antigen. Peroral administration of target autoantigens has been shown to mitigate or suppress Th1 dependent autoimmune diseases such as experimental autoimmune encephalomyelitis or collagen induced rheumatoid arthritis in rodents [9][10][11]. Dependent on the antigen dose administered there is a deletion or anergy of specific T cells, or an induction of Th2-type antigen reactive T cells.…”
mentioning
confidence: 99%